Bible, interpretation, and context: reading meaning from an African perspective - Okorie, Ferdinand (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
This book is a collection of essays that contribute to the debate on the contextual interpretation of scripture from an African context. The book engages biblical narratives from the lived experiences of Africans, insisting that meaning is attained only when people bring their daily experiences into their reading of scripture. The contributors examine the interaction of African peoples with the Bible in juxtaposition with the forces of colonialism, neocolonialism, patriarchy, war, and bad governance. This book gives voice to the lived experiences of African peoples in their quest for full expression of the profundity of their union with God by aiding them to unmask inhumanity and indignity.Book Event – Bible, Interpretation, and Context: Reading Meaning from an African Perspective